Collection Campana et sa contribution à la collection de l’art étrusque au musée de l’Ermitage - Kazanskaya, Maria (Hyperboreus, 2016)
The article presents an overview of the acquisition for the Hermitage museum of a part of the famous art collection of marquis G. P. Campana, which was negotiated in 1861 by S. A. Gedeonov. The speciﬁc case of Etruscan antiquities is used to illustrate the criteria that Gedeonov followed when choosing the articles.